Levels and trends of adolescent marriage and maternity in West and Central Africa 1986-2017 - Sagalova, Vera; Garcia, Jonathan; Bärnighausen, Till; Ntambi, John; Sodjinou, Roger; Zagre, Noel Marie; Vollmer, Sebastian (Journal of global health, 2021)
Background The world has made considerable progress in the reduction of adolescent maternity and early marriage. However, this progress has been uneven, with many countries finding themselves far from achieving the Sustainable Development Goals in this dimension. We assessed levels and trends over time in adolescent marriage and maternity prevalence within the West and Central African region as well as their correlation with select macro-level indicators for income and social institutions. Methods We estimated country-specific prevalence rates using survey data (pooled cross-sectional) conducted between 1986 and 2017. The pooled sample provides information on 262721 adolescent girls between the ages of 15 and 19. We assessed the relative country-level trends by comparing prevalence rates from the first and latest available survey in each country. We further analyzed regional trends by country income group (low- and middle-income) and examined the association of prevalence rates with measurements of gender discrimination and social institutions at the country-level. Estimations were conducted using survey weights and country-specific weights for population shares in the pooled sample. Results Prevalence of adolescent maternity declined from 30.1 percent (95% confidence interval (CI)=29.6%-32.2%) in the 1990s, to 28.7 percent (95% CI =27.9%-29.6%) in the 2000s and 26.2 percent (95% CI=25.4%-27.1%) in the 2010s. Adolescent marriage rates decreased from 37.3 percent (95% CI =35.5%-39.1%) in the 1990s to 27.5 percent (95% CI =26.5%-28.6%) in the 2000s, and to 24.9 percent (95% CI =24.1%-25.7%) in the 2010s. Between 1986 and 2017, adolescent marriage decreased in all countries except for the Central African Republic (with a rise from 39% to 55%) and Niger (56% to 61%). The prevalence of adolescent maternity decreased in all but three countries: Congo, Dem. Rep. (25% to 37%), Niger (36% to 40%), and the Central African Republic (36% to 49%). When grouped by income level, the prevalence was 8 percentage points higher in low-income countries than in middle-income countries in both outcomes. We did not establish any statisticly significant association between adolescent marriage and maternity with country-level measures of discrimination against women. However, we found evidence of an association between specific legal measures of protection against early marriage and lower prevalence rates for both early marriage and maternity. Conclusions Despite considerable progress in the reduction of adolescent maternity and marriage over the last 30 years, current levels of both indicators remain overall high in the WCA region, with high heterogeneity across individual countries. Countries with higher income level and higher standard in legal protection of young girls perform consistently better on both indicators. The prevalence rates of adolescent marriage and maternity reversed over the course of three decades, so that nowadays adolescent maternity rates exceed adolescent marriage rates in most countries. Further research is needed to understand the weak or non-existent association between adolescent marriage and maternity with gender discrimination and social institutions.